Oh Where, oh where has my little dog gone? - Trapani, Iza (Dallas, TX : Whispering Coyote Press, 1995)
An expanded version of the well-known song, in which the dog runs away from home and explores the desert, mountains, and oceans before deciding that home is best.
Keywords: Children's songs-Texts; Dogs-Songs and music -- Songs